(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
There is a high rate of casualty among miners in the world every year. One way to reduce accidents and increase safety in mines is to use the risk management process to identify and respond to major hazards in mines. The present study is an attempt to investigate the assessment and management of safety risks in Faryab chromite underground mines. In this paper, the method of AHP in type-1 and type-2 fuzzy sets is used for risk assessment. Upon studying two underground mines of Faryab chromite (Makran and Nemat), 45 hazards were divided into 9 groups, among which 7 main risks were eventually identified. The risk assessment showed that the most important hazards in the Nemat underground mine are the required airflow, the lack of proper scaling and post-blast scaling. Similarly, the assessment of hazards in the Makran underground mine showed that post-blast scaling, absence of proper scaling, and proper ventilation of dust, are the most important hazards. Finally, after detecting the causes of the accidents, based on the records of accidents at the mine safety, health, and environmental unit, technical personnel’s descriptions, and similar risk projects, proper responses are prepared for each group of hazards.